Boron Strengthened GeTe‐Based Alloys for Robust Thermoelectric Devices with High Output Power Density. Issue 37 (6th August 2021) - Bai, Guangyuan; Yu, Yuan; Wu, Xuelian; Li, Junqin; Xie, Yucheng; Hu, Lipeng; Liu, Fusheng; Wuttig, Matthias; Cojocaru‐Mirédin, Oana; Zhang, Chaohua
Abstract: High‐performance thermoelectric (TE) devices require not only a high figure of merit ( ZT ) but also mechanical strength and thermal stability. Here, a simultaneous enhancement of ZT as well as mechanical properties is obtained in GeTe‐based alloys by adding boron. This material is then assembled with n‐type CoSb3 skutterudite into TE modules. The improved ZT values result from the increase in charge carrier mobility due to the reduced interfacial barrier height. A peak ZT of 2.2 at 773 K can be achieved in Ge0.84 Pb0.1 Sb0.06 TeB0.07, which shows a negligible change in the coefficient of thermal expansion upon the phase transition from the rhombohedral to the cubic phase, ensuring good thermal stability of the device. Resulting from the boron‐induced grain refinement and dispersion strengthening, the average compressive strength and Vickers hardness of Ge0.9 Sb0.1 TeB0.07 can be enhanced to ≈227 MPa and ≈202 Hv, respectively. The improved mechanical properties facilitate the assembly of devices and lower the interfacial contact resistance. As a synergy of increased ZT and mechanical strength, a high output power density of ≈1.76 W cm −2 at Δ T = 425 K and an energy conversion efficiency of 7.4% at Δ T = 477 K can be achieved in the TE modules. Abstract : A boron‐addition strategy is proposed to enhance the thermoelectric (TE) and mechanical performance of GeTe due to the increased carrier mobility and refined grain size. A peak ZT of ≈2.2 at 773 K can be obtained in Ge0.84 Pb0.1 Sb0.06 TeB0.07, and a record‐high output power density of ≈1.76 W cm −2 under a temperature difference of 425 K can be achieved in the 8‐couple TE module.